TAX, TUNNELING ACTIVITIES, CORPORATE GOVERNANCE AND TRANSFER PRICING DECISION - Ferry Irawan; Dina Vara Sari (Bina Ekonomi, 2021)
Multinational firms consider several factors to decide transfer prices in a-related party transaction. The Purpose of this study was to determine the effect of tax, tunneling activities, and corporate governance on transfer pricing with cash holding as mediating variable. This research used a quantitative approach and panel data analysis by taking data samples from 53 manufacturing companies listed on the IDX in 2013-2019, which met the research criteria as previously set. The result stated that tunneling activities and corporate governance have a significant positive effect on transfer pricing, while the tax has negative effect on transfer pricing. Tax, tunneling activities and corporate governance has no effect on cash holding. Thus, the effect of cash holding cannot intervene the effect of tax, tunneling activities and corporate governance on transfer pricing. In the future, tax authority can narrow the scope of transfer pricing investigation by examinating elements in financial report.  Keywords: cash holding; corporate governance; transfer pricing; tax; tunneling activities